Challenges to Quit Smoking among Smokers in Bandar Baru Salak Tinggi, Sepang, Selangor, Malaysia - Nurulfarahin K.A; Nina S.A; Lailati S.; Raisah Z.; Izzuddin A A.; Sabariah Abd Hamid (International Journal of Public Health Science (IJPHS), 2018)
Cigarette smoking is the largest preventable risk factor for morbidity and mortality in developed countries.  The prevalence of smoking is increasing in Malaysia.  Over the years, we have accumulated the knowledge of the risks and dangers of smoking towards health and had used these as interventions to motivate smokers to quit smoking.  However, quitting smoking is hard as people who stop smoking often start again because of weight gain, stress and withdrawal symptoms.  Therefore, this study aimed to identify the challenges to quit smoking among smokers in Bandar Baru Salak Tinggi, Sepang, Selangor.  A cross-sectional study was conducted with a combination of stratified and simple random sampling.  The study was conducted via a face-to-face interview using a standardized questionnaire.  The data was analyzed using SPSS (Statistical Package for Social Sciences) Version 20.0.  Easy availability of cigarettes was the most challenging factor (86%) followed by seeing things that reminded the respondents of smoking (58%), feeling lost without smoking (53%) and withdrawal symptoms (47%).  To combat these challenges, it is imperative to strengthen the enforcement on regulations advertisement and display of cigarettes and develop more activities on motivation among smokers and their families, which may be organized by government or non-government organizations. Other than that, another important aspect in the promoting smoking cessation program is to encourage smoke-free homes.